2017
DOI: 10.1007/s00204-017-2068-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative developmental toxicity of a comprehensive suite of polycyclic aromatic hydrocarbons

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widespread environmental contaminants that occur in complex mixtures. Several PAHs are known or suspected mutagens and/or carcinogens, but developmental toxicity data is lacking for PAHs, particularly their oxygenated and nitrated derivatives. Such data are necessary to understand and predict the toxicity of environmental mixtures. 123 PAHs were assessed for morphological and neurobehavioral effects for a range of concentrations between 0.1 and 50 µM, using a high th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 73 publications
4
126
3
Order By: Relevance
“…In studies on the effects of maternal smoking on development, zebrafish were traditionally used as a model to examine effects of single abundant compounds of cigarette smoke. Craniofacial malformations are consistently reported in zebrafish studies on smoke compounds such as PAHs, carbon monoxide (hypoxia) and nicotine (Billiard et al, 2006;Parker and Connaughton, 2007;Geier et al, 2018;Kuchler et al, 2018). Specifically, clefts in the ethmoid plate were observed when zebrafish are exposed to hypoxic conditions during early development.…”
Section: Smokingmentioning
confidence: 96%
“…In studies on the effects of maternal smoking on development, zebrafish were traditionally used as a model to examine effects of single abundant compounds of cigarette smoke. Craniofacial malformations are consistently reported in zebrafish studies on smoke compounds such as PAHs, carbon monoxide (hypoxia) and nicotine (Billiard et al, 2006;Parker and Connaughton, 2007;Geier et al, 2018;Kuchler et al, 2018). Specifically, clefts in the ethmoid plate were observed when zebrafish are exposed to hypoxic conditions during early development.…”
Section: Smokingmentioning
confidence: 96%
“…Due to the extended holding time, it is likely that concentrations of organic chemicals decreased during this time. Previous studies have observed significant changes in LPR when zebrafish are exposed to PAHs, including carbazole, naphthalene, 1methylnaphthalene and 2-methylnaphthalene, which were all present in the PW discharge (Geier et al, 2018). Thus, it is possible that different results would have been observed if holding time was decreased.…”
Section: Zebrafish Developmental Toxicity Assaysmentioning
confidence: 97%
“…Even though transgenic zebrafish bioassays are less sensitive than many cell bioassays with similar endpoints (and are considerably more expensive to perform), the data provided by zebrafish bioassays represent a higher level of biological organization and thus may be more applicable in an EDA. For example, the pairing of transgenic in vivo bioassays with high-content imaging has provided a wealth of information at a variety of life stages on organ-and tissue-specific effects of contaminants (Keller et al 2008;Di Paolo et al 2015;Geier et al 2018). Although we could not locate a published study on EDA of EACs from water utilizing the zebrafish bioassay, E1 and 4-nonylphenol were identified by Fetter and colleagues (2014) as active components of sediment fractions by utilizing the zebrafish bioassay in an EDA study.…”
Section: Detection Approaches For Edamentioning
confidence: 99%
“…This substantially increases the volume of treatment required for each round of testing. However, it may be possible to adapt this zebrafish line to a microtiter plate format, because other zebrafish lines (such as the 5D and TG(fli1:EGFP)y1 lines) have been successfully adapted to 96-and 384-well formats for testing of environmental contaminants (Geier et al 2018;Vliet et al 2018;Dasgupta et al 2020). Differences in total treatment volume requirement should be considered when one is selecting a bioassay for the EDA.…”
Section: Water Sampling Volumesmentioning
confidence: 99%